SISTEMATIK LITERATUR REVIEW IDENTIFIKASI LAHAN GAMBUT: ANALISIS BIBLIOMETRIK - Zulkarnaini Zulkarnaini; Irfan Suliansyah; Gusmini Gusmini; Syafrimen Yasin (Fakultas Pertanian, Universitas Janabadra, 2024)
Indonesia's peatlands have the potential to be utilized for the provision of food. the purpose of this paper is to determine the development and mapping of article publications based on research topics on peatland identification. By using bibliometric analysis. The writing of this paper is descriptive qualitative using the Literature Review (LR) method. The purpose of the literature review was to search journals or literature to find the results of previous research on peatlands. Bibliographic searches were conducted using Publish or Perish (PoP) with the keyword peatland from 2010 to 2022. To map the bibliography, Vosviewer software was used. The search for articles obtained from PoP was done manually using the Google search engine. To complement the references, a literature search was also conducted through Google Scholar with the keyword Peatlands Agriculture. The bibliometric analysis in this research shows the study of the evolutionary process on the research topic with the identification of peatlands from 2010 - 2023. Vosviewer is an important programming to visualize and analyze network visualization in bibliometric analysis mapping. About 250 articles obtained from the Google Scholar database show that there is a use of the term peatland and can be a future research topic.